Silent brain ischemia within the TAXINOMISIS framework: association with clinical and advanced ultrasound metrics - Kigka, Vassiliki; Carrozzi, Alessandro; Gramegna, Laura Ludovica; Siogkas, Panagiotis K.; Potsika, Vassiliki; Tsakanikas, Vassilis; Kallmayer, Michael; Obach, Victor; Riambau, Vincente; Spinella, Giovanni; Pratesi, Giovanni; Cirillo, Luigi; et al. (Frontiers in Neurology, 2024)
INTRODUCTION The relationship between carotid artery stenosis (CAS) and ipsilateral silent brain ischemia (SBI) remains unclear, with uncertain therapeutic implications. The presented study, part of the TAXINOMISIS project (nr. 755320), focused on investigating SBIs in patients with asymptomatic CAS, correlating them with clinical and carotid ultrasonographic data, including also computational fluid dynamics (CFD) analyses. METHODS The TAXINOMISIS clinical trial study (nr. NCT03495830) involved six clinical centers of vascular surgery in Europe, enrolling patients with asymptomatic and symptomatic CAS ranging from 50% to 99%. Patients underwent carotid ultrasound and magnetic resonance imaging (MRI), including brain diffusion-weighted, T2-weighted/FLAIR, and T1-weighted sequences. Brain MRI scans were analyzed for the presence of SBI according to current definitions. Ultrasound assessments included Doppler and CFD analysis. Only asymptomatic patients were included in this substudy. RESULTS Among 195 asymptomatic patients, the mean stenosis (NASCET) was 64.1%. Thirty-three (16.9%) had at least one SBI detected on brain MRI, in detail: 19/33 (57.6%) had cortical infarcts, 4/33 (12.1%) ipsilateral lacunar infarcts, 6/33 (18.2%) subcortical infarcts, 1/33 (3.0%) both a cortical and a lacunar infarct, and 3/33 (9.1%) both a cortical and a subcortical infarct. Patients with SBIs had significantly higher risk factors including body mass index (28.52±9.38 vs 26.39±3.35, p=0.02), diastolic blood pressure (80.87±15.73 mmHg vs 80.06±8.49 mmHg, p=0.02), creatinine levels (93.66±34.61 µmol/L vs 84.69±23.67 µmol/L, p=0.02), and blood triglycerides (1.8± 1.06 mmol/L vs 1.48±0.78 mmol/L, p=0.03), along with a history of cardiovascular interventions (29.6% vs 13.8%, p=0.04), higher usage of third/fourth-line antihypertensive (50%vs16%, p=0.03) and anticoagulant medications (60% vs 16%, p=0.01), and higher number of contralateral cerebral infarcts (35.5% vs 13.4%, p<0.01 ). Moreover, carotid ultrasound revealed higher Saint Mary's Ratios (15.33± 12.45 vs 12.96±7.99, p=0.02), and CFD analysis demonstrated larger areas of low wall shear stress (0.0004±0.0004 m2 vs 0.0002±0.0002 m2, p<0.01). CONCLUSIONS The TAXINOMISIS clinical trial provides important insights into the prevalence and risk factors associated with SBIs in patients with moderate asymptomatic carotid stenosis. The associations between SBIs and certain findings further support the notion that specific hemodynamic and arterial wall characteristics may contribute to the development of silent brain infarcts.